(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
Melancholy is a concept that has traveled throughout the history of human beings. At each moment it has taken on certain characteristics. This article tries to analyze how this concept has been metamorphosed at the time of the conquest of the Inca empire by Spanish giving rise to the creation of utopia within Inca melancholy thank to the different chroniclers who gave shape to this notion